Hidden Addressing Encoding for DNA Storage - Wang, Penghao; Mu, Ziniu; Sun, Lijun; Si, Shuqing; Wang, Bin (Frontiers in Bioengineering and Biotechnology, 2022)
DNA is a natural storage medium with the advantages of small size and high storage density compared with traditional media. DNA storage can meet the current storage requirements for massive data. Owing to the limitations of DNA storage technology, the data need to be converted into short DNA sequences for storage. However, in the process, a large amount of physical redundancy will be generated to index short DNA sequences. To reduce the redundancy, this study proposes a DNA storage encoding scheme with hidden addressing. Using the improved fountain encoding scheme, the index replaces part of the data to realize hidden addresses, and then, a 40 KB file is encoded with hidden addressing. The Dottup dot plot generator and the sequence fragments of GC content are used to verify the performance of this scheme. The results show that the encoding scheme indexes with overall lower self-similarity, and the local thermodynamic properties of the sequence are better. The hidden addressing encoding scheme proposed can not only improve the utilization of bases but also ensure the correct rate of DNA storage during the sequencing and decoding processes.